SOP Used by Tour Guides in Serving Foreign Tourist at Balaputradewa Museum - Aditya, M Ihsan (Politeknik Negeri Sriwijaya, 2024)
ABSTRACT: The article aims to know the English Procedures Used by Tour Guide In Serving Foreign Tourists at Balaputradewa Museum as one of the tourism destinations in Palembang. The method used by the writer is a descriptive method. This method consists of a technique of collecting data. The data were collected through questionnaires and interviews about the information needed according to the existing phenomena. The data obtained from these methods served as the primary material for formulating the English procedures used by tour guides in serving foreign tourists at the museum. The developed procedures aim to improve the quality of interactions between the tour guide and the tourist. These procedures are poised to elevate the museum's reputation as a preferred destination for foreign tourists and contribute to a more immersive and enjoyable cultural experience for visitors from around the world. Keywords: procedures, tour guide, Museum Balaputradewa